Integrasi Pendidikan Karakter Spiritual Quotient Smpit Bina Ilmi Palembang - Taufik, Ahmad; Hana, Siti; Fahruddin, Ahmad Hanif; Kirom, Askhabul Kirom (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Ideally, many people with the criteria of spiritual intelligence (spiritual quotient) can make a person independently, feel their life through various values ​​to the process of indication of the formation of other characters as desired. Based on the existing problems, at SMP IT obtained some students have ethics when interacting with other humans are considered not good, can say words that are not polite, then there are still students who do not understand the implementation of the procedure for ablution, and still being able to accompany students who are joking and able to play while practicing prayer. So that from the problem the researchers felt interested in participating in further research in accordance with the results of the study. The purpose of this study was to find out how the planning, implementation and impact of the successful implementation of spiritual quotient in shaping students with character at SMP IT Bina Ilmi Palembang. This research is a qualitative research category with a descriptive qualitative approach in the form of data describing the amount of data obtained. Techniques in collecting data using observations, interviews, documentation with seven informants. For data analysis, using data reduction, data presentation, data verification, and data triangulation. Based on the research, it shows that: 1) The spiritual quotient planning process for students with character that occurs at SMP IT Bina Ilmi is arranged at an early stage with the teachers recommending the contents of the lesson plans which include: describing learning objectives, content material with competencies according to competency achievement, organizing material based on all sequence and group, allocating time, determining methods, methods or learning procedures, determining learning resources, and determining assessment techniques, 2) Implementation of spiritual quotient in the process of character students at SMP IT Bina Ilmi is considered effective in learning, which is when carrying out learning carried out using various methods, media, and strategies then the teachers combined with the basic values ​​of Islam, after the learning process was carried out and then ended with evaluation activities both pretest, post test and daily control of students, 3) The impact of the spiritual quotient that done If there are still many students can understand and practice spiritual values ​​and basic character values, get satisfactory learning values, have enthusiasm and can be active in learning, have good manners, respect each other, and can practice discipline.